The Association Between Short-Term Air Pollution Exposure and Post-Adolescent Acne: The Evidence from a Time Series Analysis in Xi’an, China - Li X; An SJ; Liu XL; Ji AL; Cao Y; Xiang Y; Ma XY; Hu Q; Yuan ZQ; Li YF; Lu YG; Cai TJ (Clinical, Cosmetic and Investigational Dermatology, 2021)
Xiang Li,1,2,* Shu-Jie An,3,* Xiao-Ling Liu,1,* Ai-Ling Ji,4 Yi Cao,5 Ying Xiang,1 Xiang-Yu Ma,1 Qin Hu,1 Zhi-Quan Yuan,1 Ya-Fei Li,1 Yuan-Gang Lu,2 Tong-Jian Cai1 1Department of Epidemiology, College of Preventive Medicine, Army Medical University (Third Military Medical University), Chongqing, People’s Republic of China; 2Department of Plastic & Cosmetic Surgery, Daping Hospital, Army Medical University (Third Military Medical University), Chongqing, People’s Republic of China; 3Medical Department, Xijing Hospital, Air Force Medical University (Fourth Military Medical University), Xi’an, People’s Republic of China; 4Department of Preventive Medicine & Chongqing Engineering Research Center of Pharmaceutical Sciences, Chongqing Medical and Pharmaceutical College, Chongqing, People’s Republic of China; 5Department of Health Economics Management, Xijing Hospital, Air Force Medical University (Fourth Military Medical University), Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuan-Gang LuDepartment of Plastic & Cosmetic Surgery, Daping Hospital, Army Medical University, 10 Changjiang Branch Road, Daping, Chongqing, 400042, People’s Republic of ChinaTel +86-23-68757597Fax +86-23-68757596Email skin515@163.comTong-Jian Cai Email ctjcsl@fmmu.edu.cnBackground: Post-adolescent acne is a common skin disease faced by adults. However, whether air pollution (AP) serves as a risk factor for post-adolescent acne remains elusive.Aim: To determine the relationship between short-term AP exposure (within 7 days) and outpatient visits for post-adolescent acne.Methods: Daily outpatient visit data for post-adolescent acne and routinely AP data between 2010 and 2013 were collected from Xi’an, China. A generalized additive regression model was used to analyze the relationship between outpatient visits for post-adolescent acne and short-term ambient AP exposure. The gender-specific analyses were conducted as well.Results: Totally, 27,190 outpatient visits for post-adolescent acne were included. The results revealed that a 10 μg/m3 increase in PM10, SO2, and NO2 at lag 0– 7 day was associated with the increase of outpatient visits for post-adolescent acne at 0.84% (95% CI: 0.53%, 1.16%), 1.61% (95% CI: 0.12%, 3.10%), and 3.50% (95% CI: 1.60%, 5.40%), respectively. The significant positive associations of PM10, SO2, and NO2 were found at both single-lag models and moving average models. The gender-specific analyses showed that the effect estimates of PM10 was stronger for females than for males, while there was no observed gender difference in the effects of SO2 and NO2.Conclusion: Short-term exposure to AP was associated with increased outpatient visits for post-adolescent acne, especially for females in the effects of PM10.Keywords: short-term, air pollution, post-adolescent acne, adult acne, time-series analysis